Rethinking mental healthcare for refugees - Mary Bunn; Deepika Khanna; Elizabeth Farmer; Eleanor Esbrook; Heidi Ellis; Anne Richard; Stevan Weine (Elsevier, 2023)
After several years of downturn in new resettlement, the United States is projected to admit 125,000 refugees in the current fiscal year. Refugee communities have known risks of developing mental health problems due to high rates of exposure to war and conflict-related trauma and chronic stressors associated with displacement and resettlement. In this commentary, we examine limitations in the current system of mental health care available to newly arriving refugee communities and make recommendations for expanding and redesigning services to better meet the needs of culturally diverse refugee communities. This includes drawing on public health and prevention frameworks to implement a continuum of services including basic services and security, trauma-informed prevention services to meet the needs of individuals, families and communities and specialized clinical care for those that need it. Across all services, we recommend robust engagement and partnership with refugee community leaders to design and deliver programs.